2014
DOI: 10.1021/nn504329u
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Osteoclast Differentiation by Gold Nanoparticles Functionalized with Cyclodextrin Curcumin Complexes

Abstract: Gold nanoparticles (GNPs) have been previously reported to inhibit osteoclast (OC) formation. However, previous research only confirmed the osteoclastogenesis inhibitory effect under in vitro conditions. The aim of this study was to develop a therapeutic agent for osteoporosis based on the utilization of GNPs and confirm their effect both in vitro and in vivo. We prepared β-cyclodextrin (CD) conjugated GNPs (CGNPs), which can form inclusion complexes with curcumin (CUR-CGNPs), and used these to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 48 publications
1
90
0
Order By: Relevance
“…It was found that all components showed no significant cytotoxic effects up to 48 h. On the contrary, GNPs and RGNPs exhibited a slight positive effect on ADSCs proliferation where the cell viability increased at a dose-dependent manner after 48 h. It was reported that the surface ligand of the GNPs have an important influence on the cytotoxicity. 2931, 37 In this study, we used two kinds of GNPs covered with citrate and RGD, and they showed no cytotoxicity and even more enhanced cell proliferation. Therefore, this result indicates that the prepared RGNPs could be useful as a biocompatible osteo-inductive agent.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that all components showed no significant cytotoxic effects up to 48 h. On the contrary, GNPs and RGNPs exhibited a slight positive effect on ADSCs proliferation where the cell viability increased at a dose-dependent manner after 48 h. It was reported that the surface ligand of the GNPs have an important influence on the cytotoxicity. 2931, 37 In this study, we used two kinds of GNPs covered with citrate and RGD, and they showed no cytotoxicity and even more enhanced cell proliferation. Therefore, this result indicates that the prepared RGNPs could be useful as a biocompatible osteo-inductive agent.…”
Section: Resultsmentioning
confidence: 99%
“…GNPs show potential for bone-targeted drug delivery because of their ease of functionalization with drugs, targeting moieties, and polymers on gold-thiol bonds [48], as well as their intrinsic ability to upregulate OB activity [49] and downregulate OC differentiation [50,51]. In particular, GNPs can downregulate OC formation by inhibiting the function of the osteoclastogenesis promoter, RANK ligand (RANKL), and by reducing reactive oxygen species (ROS) levels [52].…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%
“…To improve CUR delivery, Heo et al . developed GNPs functionalized with β-cyclodextrin (βCD), which can stabilize CUR through the formation of βCD-CUR inclusion complexes (Figure 2b) [50]. The in vitro results demonstrated that the GNP-βCD-CUR could inhibit the OC differentiation of bone marrow-derived macrophages (BMM).…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid nanoparticles, prepared by desolvation, encapsulated curcumin with >96 % effi ciency and increased the stability of curcumin 6.7 times. Cyclodextrins were also used to improve the water solubility and stability of curcumin through the formation of inclusion complexes [ 13 ]. The complexes were tested as such and also after functionalizing gold nanoparticles.…”
Section: Phenolic Compounds From Plant Sources Delivered As Nanopartimentioning
confidence: 99%